Effectiveness of Participation in a Blog for Extra-curricular activities for Developing Students’ Critical thinking skills: A Case of Secondary School Students - Al-Harbi, Wafa Abed Munawwar; Askool, Sanaa Saleh (Journal of Educational and Psychological Sciences, 2020)
This study aims to identify the effectiveness of participation in a blog for extra-curricular activities for developing the critical thinking skills of third secondary students in Jeddah. The sample consisted of (100) students from several schools in Jeddah, Saudi Arabia randomly selected and divided into (50) experimental group, (50) control group. The study used the Semi-experimental method and conducted the Watson and Glaser test for critical thinking. The results of the study showed that there were statistically significant differences (0.05) among the experimental group (individual and cooperative) For the officer in the brother Bar dimensional test critical thinking skills for the benefit of the experimental group because of its effect for the use of a typical blog (single, cooperative).
Keywords: Blog; critical thinking; extra-curricular activities; secondary school